2021
DOI: 10.3341/kjo.2020.1115
|View full text |Cite
|
Sign up to set email alerts
|

Visual Performance and Optical Quality after Implantation of a New Generation Monofocal Intraocular Lens

Abstract: Purpose To evaluate the performance of two intraocular lenses (IOLs). The new monofocal IOL using a higher-order aspheric optic (Tecnis Eyhance ICB00) was compared to a standard monofocal IOL (Tecnis monofocal ZCB00) of the identical platform and material. Methods The medical records of the patients who had undergone cataract surgery with implantation of either the ZCB00 or the ICB00 in the dominant eye from March 2020 to August 2020 and with available data from the 3-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
47
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 31 publications
(66 reference statements)
10
47
2
1
Order By: Relevance
“… 31 Several studies also reported the excellent distance VA of the ICB00, with no difference from a typical monofocal IOL. 3 , 10 , 13 These results are consistent with the results of the present study. In the current study, the UDVA values were 0.13 ± 0.13 and 0.11 ± 0.10, and the CDVA values were 0.05 ± 0.08 and 0.03 ± 0.05 in the ZXR00 and ICB00 groups, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 31 Several studies also reported the excellent distance VA of the ICB00, with no difference from a typical monofocal IOL. 3 , 10 , 13 These results are consistent with the results of the present study. In the current study, the UDVA values were 0.13 ± 0.13 and 0.11 ± 0.10, and the CDVA values were 0.05 ± 0.08 and 0.03 ± 0.05 in the ZXR00 and ICB00 groups, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have compared ZXR00 and a standard monofocal IOL, Tecnis ZCB00 (Johnson & Johnson Vision, Santa Ana, CA, US) (ZCB00), as well as ICB00 and ZCB00 have already been reported. 11 13 …”
mentioning
confidence: 99%
“…On the other hand, this study was conducted in a retrospective manner in Asia. In line with this study, a previous study conducted in a retrospective manner in Asia showed that the Eyhance ICB00 IOL provided superior intermediate and near vision compared to the ZCB00 IOL [ 23 ]. Therefore, the effect of the Eyhance IOL for improving near vision needs to be confirmed through a large-scale study.…”
Section: Discussionsupporting
confidence: 85%
“…Likewise, within our study, the UDVA values were 0.08 ± 0.06 and 0.06 ± 0.07 and the CDVA values were 0.03 ± 0.05 and 0.03 ± 0.05 in the ZCB00 and ZFR00 groups, respectively. Previous studies have reported monocular UIVAs (at 66 cm) of 0.25 ± 0.18 [30], 0.34 ± 0.12 [29] for the ZCB00 and 0.05 ± 0.03 [8], 0.04 ± 0.09 [6] for the ZFR00, monocular UNVA (at 40 cm) of 0.48 ± 0.32 [31], 0.51 ± 0.19 [29] for the ZCB00 and 0.03 ± 0.05 [8], 0.05 ± 0.13 [6] for the ZFR00. In the current study, the monocular UIVA (at 66 cm) values were 0.33 ± 0.12 for the ZCB00 and 0.02 ± 0.05 for the ZFR00 and the monocular UNVA (at 40 cm) values were 0.48 ± 0.15 for the ZCB00 and 0.03 ± 0.06 for the ZFR00.…”
Section: Discussionmentioning
confidence: 90%
“…A previous clinical study reported results consistent with those from this study. Earlier studies reported monocular UDVAs of 0.07 ± 0.09 [21] and 0.10 ± 0.14 [29] for the ZCB00 and 0.04 ± 0.10 [9] and − 0.01 ± 0.04 [8] for the ZFR00. Earlier studies reported monocular CDVA of − 0.02 ± 0.09 [21] and 0.03 ± 0.06 [29] for the ZCB00 and − 0.02 ± 0.07 and − 0.04 ± 0.02 [10] for the ZFR00.…”
Section: Discussionmentioning
confidence: 99%